Transformations of the spatial activity manifold convey aversive information in CA3 - Albert Miguel-López; Negar Nikbahkt; Carlos Wert-Carvajal; Lena Johanna Gschossmann; Martin Pofahl; Heinz Beck; Tatjana Tchumatchenko (Proceedings of the National Academy of Sciences, 2026)
Hippocampal circuits form cognitive maps that represent spatial position and integrate contextual information, including affective cues, into episodic memory representations. We investigated how spatial and affective information are combined in the population activity of CA3 axons by analyzing the activity of intermediate-to-dorsal and dorsal-to-dorsal axons in mice navigating a linear track before, during, and after exposure to an aversive air puff stimulus. Both axonal populations maintained a robust, time-invariant activity manifold that encoded spatial information independent of affective context. Deformations of this common manifold encoded the presence of the aversive stimulus without disrupting the spatial representation. Despite differences in spatial coding, both axonal populations encoded affective information with similar efficacy. This population-level encoding was distributed similarly across place and nonplace cells. Our findings demonstrate that hippocampal CA3 axons integrate spatial and affective information within a common representational geometry while maintaining the separability of each information type.